Pengaruh Pola Pemberian Susu Formula terhadap Kejadian Diare pada Baduta - Fery Lusviana Widiany (JURNAL NUTRISIA, 2016)
Background : Malnutrition on toddler will lead to impaired growth and development, including the risk of infectious diseases. In Indonesia, diarrhea is the second killer on toddler after Accute Respiratory Tract Infection, related barriers to exclusive breastfeeding program. The prevalence of diarrhea in Indonesia fell from 9% (2007) to 3.5% (2013), but in Yogyakarta the prevalence of diarrhea is still quite large (6.6%), which affects children aged 1-4 years (12 , 2%) and infants (11.2%). Objective : To determine the effect of formula feeding pattern to the diarrhea’s incidence on children under 2 years. Methods : This observational study with cross-sectional design involves 43 children under 2 years. Children with chronic diseases, gastrointestinal disorders, and have lactose intolerance or allergy on formula milk excluded. The dependent variable is diarrhea’s incidence, the independent variables is formula feeding pattern. Outer variables are exclusive breastfeeding history, maternal age, parental education, parental income, children’s diet, and children’s disease history. Data were analyzed using univariate, bivariate, and multivariate test. Results : Exclusive breastfeeding history affects the formula feeding pattern on the childrens (p-value = 0.001), but the other outer variables have no effect. Fisher’s Exact test shows that the formula feeding pattern does not affect the diarrhea’s incidence (p-value = 1.000). Conclusions : The formula feeding pattern does not affect the diarrhea’s incidence, but influenced by the exclusive breastfeeding history on the children. Keywords : Formula feeding pattern, exclusive breastfeeding, diarrhea, children under 2 years.